Denosumab, a RANK ligand inhibitor, for the management of bone loss in cancer patients - Yee AJ (Dove Medical Press, 2012)
Andrew J Yee, Noopur S RajeDivision of Hematology-Oncology, Massachusetts General Hospital Cancer Center, Boston, MA, USAAbstract: Bone loss is a common side effect of cancer treatments, especially antihormonal treatments used in the treatment of breast and prostate cancer. Denosumab is a monoclonal antibody given subcutaneously that inhibits osteoclast activity by targeting the RANK ligand. It is effective in settings ranging from preventing skeletal-related complications in cancer patients with metastatic disease to increasing bone mineral density in patients with osteoporosis. In cancer patients with early stage disease, denosumab can attenuate bone loss from antihormonal treatments, and in prostate cancer, may reduce disease progression. Here, we will discuss the important role denosumab may play in the management of bone loss in patients with cancer.Keywords: denosumab, zoledronic acid, bone loss, breast cancer, prostate cancer